Emergency response/operating procedure competency and evaluation of human error potential at the chemical loading bay of a bulk chemical facility in Westport, Port Klang - Ng, Kok Kheng (2020)
A questionnaire survey and passive observation was conducted at a bulk terminal facility in Westport, Port Klang. The survey was conducted using a questionnaire consisting 44 elements that make up five categories, to assess the knowledge, training and skills of the operators and contract drivers, and four questions to determine the level of emergency equipment at their respective workplace or tanker truck. The observation was based on a structured checklist of procedures using the facility's operation procedures as well as NFPA standards. The objective of this study is to evaluate the competencies of the facility operators and contract drivers who are involved in loading operations at the tanker loading stand area. This activity had been rated as having the highest risk compared to all other activities in the bulk terminal facility. The study also intends to determine the error rates for each of the procedural step involved in this operation. It was found that operators on the average have failed to meet the minimum baseline score in all the five categories, namely; (i) knowledge of emergency response plan, (ii) level of training, (iii) familiarity with the emergency equipment, (iv) familiarity with the loading procedures, and (v) abilityto respond during an emergency. Contract drivers have been able to meet the minimum requirements of the last three categories mentioned above. This could be due to contract drivers having almost twice the experience in years in this type of work compared to facility operators. The emergency equipment level for both facility operators' workplace and drivers' tankers all fell below the baseline requirement. Error rates during loading operations were also found to be quite high, especially errors involving parking and positioning of the tanker (24.5%) where many incidents of the tankers brushing or hitting the overhead hoses were recorded. Next in frequency is the failure to attach the earth clamp according to procedures (i.e. before commencement of product loading) where 18.9% error was recorded. High errors involving product spills over the tanker were also recorded (between 17% and 19%) especially during nozzle insertion into and withdrawal from the compartment. The above situations are considered critical as they could lead to an accident involving fire and explosion. Poor compliance in terms of wearing of goggles and appropriate breathing masks when required were also recorded. During loading of acid, operators and drivers have completely ignored the requirement to wear full PVC chemical suit as well as full visorslbreathing masks. There was no correlation found between drivers' competencies and their ability to carry out procedures correctly. Observations suggest that this is due to the lack of enforcement and the lack of proper attitude in appreciating the safety and health procedures that were in place. It is recommended that adequate and regular briefing and training should be provided to operators, and where possible to contract drivers as well. The areas to cover include: 1) Site emergency response plan. 2) Appropriate use of personal protective equipment during loading operation. 3) The correct usage of emergency response and personal protective equipment during an emergency, such as fire or spill. 4) Familiarity with evacuation procedures and location of all emergency equipment. The facility management should ensure strict enforcement of all loading procedures to reduce the present error rate recorded. The enforcement will need to be facilitated by adequate training and familiarity with the procedures and risk exposures present at the loading stand area.